Rare earth doped ABF3 perovskite type nano luminescent material and preparation method and application thereof
By heating the hydrogenated fluoride A solution in an organic solvent and controlling the reaction conditions, a rare earth-doped ABF3 perovskite nanoluminescent material with a core-shell structure was prepared, which solved the problem of long reaction time and uncontrollable particle size in the prior art. , realizes efficient luminescence efficiency and high-order nonlinear photon avalanche upconversion.
Patent Information
- Application Number
- CN202310759587.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-06-26
AI Technical Summary
In the prior art, when preparing rare earth-doped ABF3 perovskite nanocrystals, the reaction time is long, the particle size is uncontrollable, and the hydroxyl defect affects the luminescence efficiency, making it difficult to achieve high-order nonlinear photon avalanche upconversion.
Using hydrogenated fluoride A solution to heat the reaction in organic solvents, control the reaction time and temperature, and prepare rare earth-doped ABF3 perovskite nanoluminescent materials with core-shell-like structures to reduce hydroxyl defects and realize high-order nonlinear photon avalanche upconversion .
The nanoluminescent materials have uniform morphology and adjustable particle size, which improves the luminescence efficiency, inhibits the fluorescence quenching effect, promotes cross-relaxation between rare earth ions, and realizes room temperature high-order nonlinear photon avalanche upconversion.
Smart Images

Figure CN119193147A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nano-luminescent materials, and in particular relates to a rare earth-doped ABF3 perovskite-type nano-luminescent material and a preparation method and application thereof. Background Art
[0002] The general formula of the perovskite structure is ABF3 (where A is an alkali metal ion and B is a divalent metal cation). It is an ideal rare earth doped matrix material due to its high optical transparency, low phonon energy, good thermal stability, anisotropy and wide band gap. At present, the methods for preparing rare earth doped ABF3 perovskite nanocrystals mainly include water / solvent thermal and high temperature coprecipitation methods. Among them, the water / solvent thermal method has a long reaction time, and the prepared nanocrystals are easy to agglomerate and the particle size is uncontrollable. In addition, when using this method to prepare nanocrystals, the hydroxyl groups in the reaction system can easily replace the fluoride ions and enter the interior of the nanocrystals, forming hydroxyl defects, resulting in severe quenching of the luminescence of the nanocrystals. The high temperature coprecipitation method for preparing nanocrystals has a mild reaction and the reaction conditions are easy to control. The method can obtain monodispersed rare earth doped nanocrystals. However, the previous scientific researchers used NH4F and AOH as fluorine sources and A sources to prepare ABF3 perovskite nanocrystals using this method. The use of AOH increases the hydroxyl content in the system. A large number of hydroxyl groups participate in the nucleation and growth process of nanocrystals, resulting in a large number of hydroxyl defects on the surface and inside of the nanocrystals, thereby affecting the luminescence efficiency of the nanocrystals. In addition, the nanocrystals prepared using NH4F as the fluorine source have a small particle size, making it difficult to control the particle size of the nanocrystals. Limited by the types of reaction precursors and preparation methods, the preparation of rare earth-doped ABF3 perovskite nanocrystals with efficient luminescence is still a major problem.
[0003] Rare earth doped photon avalanche upconversion nanocrystals have broad application prospects in cutting-edge technologies such as super-resolution bioimaging, micro-lasers, single-molecule tracing and quantum optics. However, due to the fluorescence quenching effect of surface and internal hydroxyl defects of nanocrystals, the realization of high-order nonlinear photon avalanche upconversion of rare earth nanocrystals at room temperature is still a major challenge in the field of rare earth luminescence. Due to the alivalent doping of rare earth ions in ABF3, rare earth ion clusters are easily formed, which can promote the cross-relaxation process between rare earth ions and is conducive to the realization of photon avalanche upconversion process. Therefore, the development of new synthesis technology to achieve the controlled synthesis of efficient rare earth doped ABF3 perovskite nanoluminescent materials is of great significance for the realization of high-order nonlinear photon avalanche upconversion of rare earth ions and its application in super-resolution imaging and other fields. Summary of the invention
[0004] In order to improve the deficiencies of the prior art, the present invention provides a rare earth doped ABF3 perovskite type nano luminescent material, the general formula of the luminescent material is ABF3: x mol% Ln n+, wherein A is selected from at least one of alkali metals Li, Na, K, Rb, Cs; B is selected from at least one of alkaline earth metals or transition group metals Mg, Ca, Sr, Ba, Mn, Zn, Cd, Co, Ni, Cu; F represents fluorine element, and Ln represents lanthanide rare earth element; x mol% represents the percentage of lanthanide rare earth ions in the total number of moles of alkaline earth metals or transition group metals and lanthanide rare earth elements, 0 < x ≤ 80; n is 2 or 3.
[0005] According to an embodiment of the present invention, the A is K and / or Na.
[0006] According to an embodiment of the present invention, the B is Mg and / or Zn.
[0007] According to an embodiment of the present invention, the Ln n+ is selected from Ho 3+ , Er 3+ , Tm 3+ , Tb 3+ , Eu 3+ , Eu 2+ , Ce 3+ , Sm 3+ , Sm 2+ , Dy 3+ , Nd 3+ , Pr 3+ , Gd 3+ , Sc 3+ , Lu 3+ , Yb 3+ , Yb 2+ , Y 3+ , La 3+ and at least one of them, preferably Yb 3+ , Er 3+ , Ho 3 + , Tm 3+ and at least one of them.
[0008] According to an embodiment of the present invention, 0.0001% ≤ x ≤ 80, preferably 0.01 ≤ x ≤ 40, more preferably 1 ≤ x ≤ 40, still more preferably 1 ≤ x ≤ 30. Exemplarily, x is 0.01, 1, 2, 3, 5, 10, 15, 20, 25, 30, 35, 40.
[0009] According to an embodiment of the present invention, the luminescent material is KMgF3:20mol%Yb 3+ , 2mol%Er 3+ , KMgF3:20mol%Yb 3+ , 1mol%Ho 3+ , KMgF3:1mol%Yb 3+、KMgF3:5mol%Yb 3+ 、KMgF3:10mol%Yb 3+ 、KMgF3:20mol%Yb 3+ 、KMgF3:30mol%Yb 3+ , or KMgF3:1mol%Tm 3+ 、KMgF3:3mol%Tm 3+ 、KMgF3:5mol%Tm 3+ or NaMgF3:5mol%Yb 3+ or KZnF3:2mol%Yb 3+ .
[0010] According to an embodiment of the present invention, the particle size of the luminescent material is 5-200 nm, preferably 10-50 nm, and exemplarily is 10 nm, 12 nm, 17 nm, 20 nm, 21 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm.
[0011] According to an embodiment of the present invention, the luminescent material is a core-shell structure, wherein the central region is a rare earth element and the peripheral region is A, B and fluorine elements.
[0012] According to an embodiment of the present invention, the light-emitting material is in a cubic phase or an orthorhombic phase.
[0013] According to an embodiment of the present invention, the nano-luminescent material can realize high-order nonlinear photon avalanche up-conversion at room temperature.
[0014] The present invention also provides a method for preparing the rare earth-doped ABF3 perovskite-type nano-luminescent material, the method comprising:
[0015] The B salt, the Ln salt and the A hydrofluoride are dissolved in an organic solvent and heated for reaction to obtain the rare earth doped ABF3 perovskite type nano luminescent material.
[0016] Wherein, A, B, and Ln have the definitions described above.
[0017] According to an embodiment of the present invention, the hydrofluoride A is added in the form of a solution. The hydrofluoride A solution is prepared by dissolving hydrofluoride A in water or an alcohol solvent, such as ethanol, methanol, etc. The concentration of the hydrofluoride A solution is 1-5 mol / L, preferably 1.5-4 mol / L.
[0018] Preferably, the method comprises the following steps:
[0019] (1) dissolving B salt and Ln salt in an organic solvent to form a salt solution;
[0020] (2) adding a fluoride hydrogen A solution to the salt solution obtained in step (1); heating the reaction to prepare the rare earth-doped ABF3 perovskite-type nano-luminescent material.
[0021] According to an embodiment of the present invention, the heating reaction time is 1-240 minutes, preferably 30-180 minutes. The present invention adopts different reaction times to obtain ABF3 perovskite nanoluminescent materials of different sizes, morphologies and luminescent properties; within the time range of the present invention, if other conditions remain unchanged, the longer the reaction time, the larger the size of the obtained luminescent material, the better its luminescent properties, and the higher the luminescent efficiency.
[0022] According to an embodiment of the present invention, the temperature of the heating reaction is 100-400°C, preferably 200-330°C, exemplarily 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C. The present invention adopts different reaction temperatures to obtain ABF3 perovskite nano-luminescent materials of different sizes, morphologies and luminescent properties; within the temperature range of the present invention, if other conditions remain unchanged, the higher the reaction temperature, the larger the size of the luminescent material, the better its luminescent properties, and the higher the luminescent efficiency.
[0023] According to an embodiment of the present invention, the B salt is selected from a halide, acetate, nitrate, oxalate, acetylacetonate, or a crystalline hydrate thereof containing B; preferably an acetate or a crystalline hydrate thereof containing B. For example, at least one selected from Mg(CH3COO)2, Ca(CH3COO)2, Sr(CH3COO)2, Ba(CH3COO)2, Mn(CH3COO)2, Zn(CH3COO)2, Cd(CH3COO)2, Co(CH3COO)2, Cu(CH3COO)2, or Ni(CH3COO)2.
[0024] According to an embodiment of the present invention, the Ln salt is selected from at least one of Ln-containing halides, acetates, nitrates, oxalates, acetylacetonates, or crystalline hydrates of these salts. For example, one or more selected from La(CH3COO)3, Ce(CH3COO)3, Pr(CH3COO)3, Nd(CH3COO)3, Sm(CH3COO)3, Eu(CH3COO)3, Gd(CH3COO)3, Tb(CH3COO)3, Dy(CH3COO)3, Ho(CH3COO)3, Er(CH3COO)3, Tm(CH3COO)3, Yb(CH3COO)3, Lu(CH3COO)3, Y(CH3COO)3, Sc(CH3COO)3, preferably at least one of Yb(CH3COO)3·4H2O, Er(CH3COO)3·4H2O, Ho(CH3COO)3·4H2O, Tm(CH3COO)3·4H2O.
[0025] According to an embodiment of the present invention, the organic solvent is selected from at least one of oleic acid, oleylamine, trioctylamine and octadecene, preferably a mixture of oleic acid and octadecene.
[0026] According to an embodiment of the present invention, when the organic solvent is a mixed solvent, it is a mixture of oleic acid, oleylamine and octadecene; the volume ratio of oleic acid, oleylamine and octadecene is (1-10):(0-10):(1-100), preferably (1-6):(0-6):(1-50), and further preferably (1-2):(0-6):(2-6), for example, 1:2:2, 2:3:5, 1:3:6 or 2:0:3.
[0027] According to the preparation method of the present invention, the reaction is carried out under the protection of an inert gas; the inert gas is, for example, nitrogen.
[0028] According to the preparation method of the present invention, the molar ratio of B salt to Ln salt is (1-x):x.
[0029] According to the preparation method of the present invention, the amount of hydrofluoride A used is 1 to 5 times the sum of the molar numbers of B salt and Ln salt, preferably 1 to 3 times, and more preferably 1.5 times.
[0030] According to an embodiment of the present invention, the method further comprises a post-processing step: cooling, centrifuging, washing, drying, etc. the prepared product.
[0031] According to an embodiment of the present invention, the centrifugation refers to separating the obtained precipitate from the reaction system and obtaining a solid product by centrifugal separation; the washing is to remove the organic solvent remaining on the surface of the solid product; the washing method can be filtering washing or centrifugal washing; the washing can be carried out using an organic solvent such as acetone, acetonitrile, n-butanol, isopropanol, tert-butanol, ether, methyl ethyl ketone, octane, cyclohexane or toluene, preferably ethanol and / or cyclohexane. For example, the drying temperature is 30-100°C, preferably 50-80°C.
[0032] In the present invention, the washed product is dried to obtain rare earth doped ABF3 perovskite type nano luminescent material solid powder.
[0033] According to an embodiment of the present invention, the method further comprises: dispersing the rare earth doped ABF3 perovskite type nano luminescent material in a non-polar organic solvent to obtain a rare earth doped ABF3 perovskite type nano luminescent material solution.
[0034] According to an embodiment of the present invention, the non-polar organic solvent is selected from at least one of n-hexane, cyclohexane, chloroform, dichloromethane or toluene, preferably cyclohexane and / or toluene.
[0035] The present invention also provides applications of the rare earth doped ABF3 perovskite nanoluminescent material in the fields of fluorescence detection, biological imaging, super-resolution imaging, single molecule tracing, optical anti-counterfeiting and encoding, etc. Preferably, it is used in the fields of fluorescence detection and super-resolution imaging.
[0036] Beneficial effects of the present invention:
[0037] 1. The synthesis conditions of the preparation method of the present invention are easy to control. The synthesized luminescent material has uniform morphology, monodisperse, adjustable particle size and spontaneously generates a core-shell structure, which can effectively reduce the fluorescence quenching effect on the surface of the luminescent material, and effectively reduce the hydroxyl content in the reaction system, inhibit the generation of hydroxyl defects inside the luminescent material, and improve the luminescence efficiency of the luminescent material.
[0038] 2. The luminescent material of the present invention can synthesize the target product in a wide temperature range of 100 to 400° C. The controllable preparation of the luminescent material can be achieved by changing the solvent ratio, reaction temperature and / or reaction time.
[0039] 3. The hydroxyl defects inside the luminescent material of the present invention are effectively suppressed, and the rare earth ions are asymmetrically doped therein, which can promote cross relaxation between the rare earth ions and realize high-order nonlinear photon avalanche upconversion of the luminescent material at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1KMgF3:20mol%Yb with different particle sizes (particle sizes of 12, 17, 21 and 30 nm, respectively) in Example 1 3+ ,2mol%Er 3+ X-ray powder diffraction pattern of nanocrystals.
[0041] Figure 2 KMgF3:20mol%Yb with different particle sizes (particle sizes of 12, 17, 21 and 30 nm, respectively) in Example 1 3+ ,2mol%Er 3+ Transmission electron microscopy images of nanocrystals and their corresponding particle size statistics.
[0042] Figure 3 30nm KMgF3:20mol%Yb in Example 1 3+ ,2mol%Er 3+ (a) Annular dark-field scanning electron microscopy of nanocrystals, (b) single particle energy loss, (c) F, (d) Mg, (e) K, (f) Yb, (g) Er and (h) overlay of the distribution of the above elements.
[0043] Figure 4 (a) KMgF3:20mol%Yb with different particle sizes in Example 1 at room temperature and 980nm excitation 3+ ,2mol%Er 3+ Nanocrystals, (b) KMgF3:20mol%Yb with different particle sizes in Example 2 3+ ,1mol%Ho 3+ Upconversion and downconversion luminescence spectra of nanocrystals, (c, d) Er 3+ of 4 F 9 / 2 Energy level and 4 I 13 / 2 Fluorescence decay curve of energy level, (e,f)Ho 3+ of 5 F4 and 5 Fluorescence decay curve of I6 energy level.
[0044] Figure 5 For different Yb in Example 3 3+ Doping concentration KMgF3:x mol% Yb 3+ (x=0, 1, 5, 10, 20, 30) X-ray powder diffraction patterns of nanocrystals.
[0045] Figure 6 In Example 3, (ac) is different Yb 3+ Doping concentration KMgF3:x mol% Yb 3+ The transmission electron microscopy (df) of nanocrystals (x=1, 10, 20) is the corresponding high-resolution transmission electron microscopy image.
[0046] Figure 7 At room temperature, KMgF3:5mol%Tm in Example 4 3+ Upconversion emission spectra of nanocrystals under 1064nm excitation and different excitation power densities.
[0047] Figure 8 At room temperature, different Tm in Example 4 3+ Doping concentration KMgF3:x mol%Tm 3+ (x=1, 3, 5), under 1064nm excitation, (a) KMgF3:x mol%Tm 3+ In nanocrystals, Tm 3+ 802nm( 3 H4→ 3 H6), the dotted line is the linear fit at the maximum slope of the nonlinear curve (excitation wavelength is 1064nm); (b) KMgF3: xmol% Tm 3+ The nonlinear curve of nanocrystals is linearly fitted to obtain the relationship between the corresponding slope and the excitation power density.
[0048] Fig. 9 At room temperature, under 1064nm excitation in Example 4, KMgF3: 5mol%Tm 3+ Time-resolved upconversion spectroscopy of nanocrystals.
[0049] Fig.10 At room temperature, NaMgF3:5mol%Yb in Example 5 3+ X-ray powder diffraction pattern of nanocrystals.
[0050] Fig.11 At room temperature, KZnF3:2mol%Yb in Example 6 3+ X-ray powder diffraction pattern of nanocrystals. DETAILED DESCRIPTION
[0051] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0052] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0053] Instruments and equipment:
[0054] The powder diffraction characterization of the product of the embodiment of the present invention is performed using an instrument of model MiniFlex2 manufactured by Rigaku, and the radiation wavelength of the copper target is λ=0.154187 nm.
[0055] The instrument model used for X-ray energy spectrum analysis of the product in the embodiment of the present invention is JEM-2010, and the manufacturer is JEOL.
[0056] The transmission electron microscope used for the product of the embodiment of the present invention is a TECNAI G 2 F20, manufactured by FEI.
[0057] The instrument model used for the fluorescence emission spectrum and fluorescence lifetime characterization of the product in the embodiment of the present invention is FLS980, the manufacturer is Edinburgh, and the excitation light source is a xenon lamp and a 980nm LD laser.
[0058] The instrument model used for characterizing the photon avalanche power dependence and time-resolved spectrum of the product of the embodiment of the present invention is Ti-U, the manufacturer is Nikon, and the excitation light source is 1064nm LD laser.
[0059] Example 1: KMgF3:20mol%Yb with different particle sizes 3+ ,2mol%Er 3+ Preparation of nanocrystals.
[0060] Weigh 0.78mmol Mg(CH3COO)2·H2O, 0.20mmol Yb(CH3COO)3·4H2O and 0.02mmol Er(CH3COO)3·4H2O at room temperature. Add 8mL oleic acid and 12mL octadecene, mix well, heat to dissolve under nitrogen atmosphere, and stir well. Cool to room temperature, add 1.5mmol potassium bifluoride aqueous solution (concentration is 1.5mol / L), heat to a certain temperature under nitrogen atmosphere, react for a certain time, cool to room temperature, use ethanol for precipitation centrifugation and washing, and prepare KMgF3:20mol%Yb 3+ ,2mol%Er 3+ Nanocrystals, that is, luminescent materials.
[0061] Specifically, the reaction temperature and reaction time of different particle sizes are as follows: (a) 12nm: 280℃, reaction for 1h; (b) 17nm: 280℃, reaction for 2h; (c) 21nm: 290℃, reaction for 1h; (b) 30nm: 290℃, reaction for 2h.
[0062] Figure 1 KMgF3:20mol%Yb with different particle sizes (particle sizes of 12, 17, 21 and 30 nm, respectively) in Example 13+ ,2mol%Er 3+ X-ray powder diffraction pattern of nanocrystals.
[0063] Figure 1 It shows that KMgF3:20mol%Yb prepared under different reaction conditions 3+ ,2mol%Er 3+ The nanocrystals have good crystallinity, which is consistent with the PDF standard card (JCPDS No.018-1033) of cubic phase KMgF3 crystals, and no extra diffraction peaks appear, indicating that the nanocrystals prepared under different reaction conditions are all pure cubic phase KMgF3.
[0064] Figure 2 KMgF3:20mol%Yb with different particle sizes (particle sizes of 12, 17, 21 and 30 nm, respectively) in Example 1 3+ ,2mol%Er 3+ Transmission electron microscopy images of nanocrystals and their corresponding particle size statistics.
[0065] Figure 2 It shows that the nanocrystals prepared under different reaction conditions have good dispersion and uniform morphology, and the particle sizes are 12.1nm, 17.0nm, 21.3nm and 30.8nm, respectively.
[0066] Figure 3 KMgF3:20mol%Yb with a particle size of 30nm in Example 1 3+ ,2mol%Er 3+ (a) Annular dark-field scanning electron microscopy of nanocrystals, (b) single particle energy loss, (c) F, (d) Mg, (e) K, (f) Yb, (g) Er and (h) overlay of the distribution of the above elements.
[0067] Figure 3 It shows that KMgF3:20mol%Yb 3+ ,2mol%Er 3+ Potassium, magnesium, fluorine and doped rare earth elements ytterbium and erbium exist in the nanocrystals, and the rare earth ions gather in the center to form a structure similar to KMgF3:xmol%Ln 3+ @KMgF3 core-shell structure, the brighter central area corresponds to the rare earth elements with heavier molecular weight in the nanocrystals, and the darker outer area corresponds to the potassium, magnesium and fluorine elements with lighter molecular weight in the nanocrystals.
[0068] Figure 4 (a) KMgF3:20mol%Yb with different particle sizes in Example 1 at room temperature and 980nm excitation 3+ ,2mol%Er 3+ Nanocrystals, and (c, d) Er 3+of 4 F 9 / 2 Energy level and 4 I 13 / 2 Fluorescence decay curve of energy level, (e,f)Ho 3+ of 5 F4 and 5 Fluorescence decay curve of I6 energy level.
[0069] Figure 4 a, c, d show that at 980 nm (excitation power density of 20 W cm –2 ) excitation, KMgF3:20mol%Yb 3+ ,2mol%Er 3+ The nanocrystals exhibit bright red upconversion luminescence, and the emission spectrum shows that Er 3+ The characteristic peak emissions at 521, 542, 653 and 1528 nm are respectively attributed to Er 3+ of 2 H 11 / 2 → 4 I 15 / 2 , 4 S 3 / 2 → 4 I 15 / 2 , 4 F 9 / 2 → 4 I 15 / 2 and 4 I 13 / 2 → 4 I 15 / 2 As the size of nanocrystals increases, the surface fluorescence quenching weakens, the luminescence of nanocrystals gradually increases, and the fluorescence decay slows down.
[0070] Example 2: KMgF3:20mol%Yb with different particle sizes 3+ ,1mol%Ho 3+ Preparation of nanocrystals.
[0071] Weigh 0.79mmol Mg(CH3COO)2·H2O, 0.20mmol Yb(CH3COO)3·4H2O and 0.01mmol Ho(CH3COO)3·4H2O at room temperature. Add 8mL oleic acid and 12mL octadecene, mix well, heat to dissolve under nitrogen atmosphere, and stir well. Cool to room temperature, add 1.5mmol potassium bifluoride aqueous solution (concentration is 1.5mol / L), heat to a certain temperature under nitrogen atmosphere, react for a certain time, cool to room temperature, use ethanol for precipitation centrifugation and washing, and prepare KMgF3:20mol%Yb 3+ ,1mol%Ho 3+ Nanocrystals, that is, luminescent materials.
[0072] Specifically, the reaction temperature and reaction time for different particle sizes are as follows: (a) 12 nm: 280 ° C, reaction for 1 h; (b) 17 nm: 280 ° C, reaction for 2 h; (c) 21 nm: 290 ° C, reaction for 1 h; (b) 30 nm: 290 ° C, reaction for 2 h.
[0073] Figure 4 b is the KMgF3:20mol%Yb with different particle sizes in Example 2 under 980nm excitation at room temperature. 3+ ,1mol%Ho 3+ Up-conversion and down-conversion luminescence spectra of nanocrystals.
[0074] Figure 4 b, e, and f show that at 980 nm (excitation power density of 20 W cm –2 ) excitation, KMgF3:20mol%Yb 3+ ,1mol%Ho 3+ The nanocrystals exhibit bright green upconversion luminescence, and the emission spectrum shows that Ho 3+ The characteristic peak emissions at 545nm, 659nm, 750nm and 1197nm are respectively attributed to Ho 3+ of 5 F4→ 5 I8, 5 F5→ 5 I8, 5 F4→ 5 I7 and 5 I6→ 5 The electronic transition of I8. As the particle size of nanocrystals increases, their specific surface area decreases, the fluorescence quenching effect weakens, the luminescence of nanocrystals increases, and the fluorescence lifetime lengthens.
[0075] Example 3: Different Yb 3+ Doping concentration KMgF3:x mol% Yb 3+ Preparation of nanocrystals.
[0076] Weigh (1-x)mmol Mg(CH3COO)2·H2O, x mmol Yb(CH3COO)3·4H2O (x=0, 0.01, 0.05, 0.1, 0.2, 0.3) at room temperature. Add 8mL oleic acid and 12mL octadecene, mix well, heat to dissolve under nitrogen atmosphere, and stir well. Cool to room temperature, add 1.5mmol potassium bifluoride aqueous solution (concentration is 1.5mol / L), heat to 290℃ under nitrogen atmosphere, keep warm for 2h, and cool to room temperature. Use ethanol for precipitation centrifugation washing to obtain oil-soluble KMgF3:x mol%Yb with good dispersibility. 3+Nanocrystals (x=0, 1, 5, 10, 20, 30), i.e., luminescent materials.
[0077] Figure 5 For different Yb in Example 3 3+ Doping concentration KMgF3:x mol% Yb 3+ (x=0, 1, 5, 10, 20, 30) X-ray powder diffraction patterns of nanocrystals.
[0078] Figure 5 It shows that different Yb 3+ The doped KMgF3 nanocrystals have good crystallization, and the diffraction peaks are consistent with the PDF standard card of cubic phase KMgF3 crystals (JCPDS No.018-1033). 3+ As the doping concentration increases, the peak width of the diffraction peak of KMgF3 nanocrystals gradually narrows, and the particle size of the nanocrystals gradually increases; the position of the diffraction peak gradually shifts to a small angle, indicating that Yb 3+ Replace Mg with smaller radius 2+ The lattice sites cause the lattice to expand.
[0079] Figure 6 In Example 3, (ac) is different Yb 3+ Doping concentration KMgF3:x mol% Yb 3+ The transmission electron microscopy (df) of nanocrystals (x=1, 10, 20) is the corresponding high-resolution transmission electron microscopy image.
[0080] Figure 6 af indicates that as Yb 3+ As the doping concentration increases, the particle size of the nanocrystals gradually increases, indicating that rare earth ions can promote the growth and formation of nanocrystals; the lattice expansion of KMgF3 nanocrystals, the lattice fringe width of the nanocrystal (110) crystal plane increases from 0.27nm to 0.29nm, further indicating that Yb 3+ Replaced Mg 2+ The position of.
[0081] Example 4: KMgF3:x mol%Tm 3+ Preparation of nanocrystals.
[0082] Weigh (1-x)mmol Mg(CH3COO)2·H2O, x mmol Tm(CH3COO)3·4H2O (x=0.01, 0.03, 0.05) at room temperature. Add 8mL oleic acid and 12mL octadecene, mix well, heat to dissolve under nitrogen atmosphere, and stir well. Cool to room temperature, add 1.5mmol potassium bifluoride aqueous solution (concentration is 1.5mol / L), heat to 290℃ under nitrogen atmosphere, keep warm for 2h, and cool to room temperature. Use ethanol for precipitation centrifugation washing to obtain oil-soluble KMgF3:x mol% Tm with good dispersibility. 3+ Nanocrystals (x=1, 3, 5).
[0083] Figure 7 At room temperature, KMgF3:5mol%Tm in Example 4 3+ Upconversion emission spectra of nanocrystals under 1064nm excitation at different excitation power densities.
[0084] Figure 7 It shows that at 1064nm (power density of 15.1kW cm –2 ) excitation, KMgF3:5mol%Tm 3+ Nanocrystals exhibit Tm at 802nm 3+ ( 3 H4→ 3 The characteristic emission peak of H6 is 3 kW cm –2 ) excitation, in addition to the 802nm emission peak, Tm 3+ At 662nm( 1 G4→ 3 F4) and 709nm( 3 F 2,3 → 3 H6) at the characteristic emission peak.
[0085] Figure 8 At room temperature, different Tm in Example 4 3+ Doping concentration KMgF3:x mol%Tm 3+ (x=1, 3, 5), under 1064nm excitation, (a) KMgF3:x mol%Tm 3+ In nanocrystals, Tm 3+ 802nm( 3 H4→ 3 H6), the dotted line is the linear fit at the maximum slope of the nonlinear curve (excitation wavelength is 1064nm); (b) KMgF3: xmol% Tm 3+The nonlinear curve of nanocrystals is linearly fitted to obtain the relationship between the corresponding slope and the excitation power density.
[0086] Figure 8 Indicates Tm 3+ As the doping concentration increases from 1mol% to 5mol%, the ESA-CR energy cycling rate increases. 3+ Tm in nanocrystals 3+ The maximum slope s of the linear fitting curve between the luminescence intensity at 802 nm and the excitation light power density at 1064 nm increased from 23.4 to 27.0. At the same time, the threshold power density also increased from 25.6 kW cm -2 Reduced to 16.6kWcm -2 In KMgF3:x mol%Tm 3+ There is a clear threshold power in the nanocrystals. Beyond this threshold power, the emission intensity shows a nonlinear growth, which is consistent with the characteristics of photon avalanche, indicating that photon avalanche upconversion exists in them.
[0087] Fig. 9 At room temperature, under 1064nm excitation in Example 4, KMgF3: 5mol%Tm 3+ Time-resolved upconversion spectroscopy of nanocrystals.
[0088] Fig. 9 It shows that KMgF3:5mol%Tm 3+ The rise time of excited state fluorescence lifetime of nanocrystals increases gradually near the threshold power. -2 The maximum rise time of excited state lifetime is 281ms at the threshold power, and the rise time of excited state fluorescence lifetime is prolonged at the threshold power, which further indicates that in KMgF3:5mol%Tm 3+ Nanocrystals have photon avalanche upconversion. And in KMgF3:x mol%Tm 3+ In nanocrystals, the rise time of excited state fluorescence lifetime is shorter than the rise time of conventional photon avalanche (seconds to minutes), indicating that in KMgF3:x mol% Tm 3+ In nanocrystals, Tm 3+ The photon avalanche response is faster.
[0089] Example 5: NaMgF3:5mol%Yb 3+ Preparation of nanocrystals.
[0090] Weigh 0.95mmol Mg(CH3COO)2·H2O and 0.05mmol Yb(CH3COO)3·4H2O at room temperature. Add 8mL oleic acid and 12mL octadecene, mix well, heat to dissolve under nitrogen atmosphere, and stir well. Cool to room temperature, add 1.5mmol sodium bifluoride aqueous solution (concentration is 1.5mol / L), heat to 290℃ under nitrogen atmosphere, keep warm for 1h, and cool to room temperature. Use ethanol for precipitation centrifugation washing to obtain oil-soluble NaMgF3:5mol%Yb with good dispersibility. 3+ Nanocrystals, that is, luminescent materials.
[0091] Fig.10 At room temperature, NaMgF3:5mol%Yb in Example 5 3+ X-ray powder diffraction pattern of nanocrystals.
[0092] Fig.10 It shows that the prepared NaMgF3:5mol%Yb 3+ The nanocrystals have good crystallinity, which is consistent with the PDF standard card (JCPDS No.900-3812) of orthorhombic NaMgF3 crystals, and no extra diffraction peaks appear, indicating that the prepared nanocrystals are pure orthorhombic NaMgF3 phase.
[0093] Example 6: KZnF3:2mol%Yb 3+ Preparation of nanocrystals.
[0094] Weigh 0.98mmol Zn(CH3COO)2·H2O and 0.02mmol Yb(CH3COO)3·4H2O at room temperature. Add 6mL oleic acid and 15mL octadecene, mix well, heat to dissolve under nitrogen atmosphere, and stir well. Cool to room temperature, add 1.5mmol potassium bifluoride aqueous solution (concentration is 1.5mol / L), heat to 290℃ under nitrogen atmosphere, keep warm for 1h, and cool to room temperature. Use ethanol to centrifuge and wash the precipitate to obtain oil-soluble KZnF3:2mol%Yb with good dispersibility. 3+ Nanocrystals, that is, luminescent materials.
[0095] Fig.11 At room temperature, KZnF3:2mol%Yb in Example 6 3+ X-ray powder diffraction pattern of nanocrystals.
[0096] Fig.11 It shows that the prepared KZnF3:2mol%Yb 3+The nanocrystals have good crystallinity, which is consistent with the PDF standard card (JCPDS No.089-4110) of cubic phase KZnF3 crystals, and no extra diffraction peaks appear, indicating that the prepared nanocrystals are pure cubic phase KZnF3.
[0097] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A rare earth doped ABF3 perovskite type nano luminescent material, characterized in that: The general formula of the luminescent material is ABF3:x mol% Ln n+ , where A is selected from at least one of alkali metals Li, Na, K, Rb, Cs; B is selected from at least one of alkaline earth metals or transition metals Mg, Ca, Sr, Ba, Mn, Zn, Cd, Co, Ni, Cu; F represents fluorine element, and Ln represents lanthanide rare earth element; x mol% represents the percentage of lanthanide rare earth ions in the total number of moles of alkaline earth metals or transition metals and lanthanide rare earth elements, 0 < x ≤ 80; n is 2 or 3.
2. The material according to claim 1, characterized in that The A is K and / or Na; the B is Mg and / or Zn. Preferably, the Ln n+ Selected from Ho 3+ , Er 3+ 、Tm 3+ , Tb 3+ 、Eu 3+ 、Eu 2+ 、Ce 3+ 、Sm 3+ 、Sm 2+ 、Dy 3+ 、Nd 3+ , Pr 3+ , Gd 3 + Sc 3+ 、Lu 3+ , Yb 3+ , Yb 2+ , Y 3+ ,La 3+ At least one of, preferably Yb 3+ , Er 3+ 、Ho 3+ 、Tm 3+ At least one of .
3. The material according to claim 1 or 2, characterized in that 0.0001%≤x≤80, preferably 0.01≤x≤40, preferably 1≤x≤40. Preferably, the luminescent material is KMgF3:20mol%Yb 3+ ,2mol%Er 3+ 、KMgF3:20mol%Yb 3+ ,1mol%Ho 3+ 、KMgF3:1mol%Yb 3+ 、KMgF3:5mol%Yb 3+ 、KMgF3:10mol%Yb 3+ 、KMgF3:20mol%Yb 3+ 、KMgF3:30mol%Yb 3+ , or KMgF3:1mol%Tm 3+ 、KMgF3:3mol%Tm 3+ 、KMgF3:5mol%Tm 3+ or NaMgF3:5mol%Yb 3+ or KZnF3:2mol%Yb 3+ .
4. The material according to any one of claims 1 to 3, characterized in that The particle size of the luminescent material is 5-200 nm. Preferably, the luminescent material is a core-shell structure, wherein the central region is a rare earth element and the peripheral region is A, B and fluorine elements. Preferably, the luminescent material is in a cubic phase or an orthorhombic phase. Preferably, the luminescent material can achieve high-order nonlinear photon avalanche upconversion at room temperature.
5. The method for preparing the material according to any one of claims 1 to 4, characterized in that: The method comprises: dissolving B salt, Ln salt and A hydrofluoride in an organic solvent, heating for reaction, and obtaining the rare earth-doped ABF3 perovskite-type nano-luminescent material.
6. The method according to claim 5, characterized in that The heating reaction time is 1-240 minutes; the heating reaction temperature is 100-400°C. Preferably, the B salt is selected from a halide, acetate, nitrate, oxalate, acetylacetonate, or a crystalline hydrate thereof containing B; preferably an acetate or a crystalline hydrate thereof containing B. For example, at least one selected from Mg(CH3COO)2, Ca(CH3COO)2, Sr(CH3COO)2, Ba(CH3COO)2, Mn(CH3COO)2, Zn(CH3COO)2, Cd(CH3COO)2, Co(CH3COO)2, Cu(CH3COO)2, or Ni(CH3COO)2. Preferably, the Ln salt is selected from at least one of Ln-containing halides, acetates, nitrates, oxalates, acetylacetonates, or crystalline hydrates of these salts. For example, it is selected from one or more of La(CH3COO)3, Ce(CH3COO)3, Pr(CH3COO)3, Nd(CH3COO)3, Sm(CH3COO)3, Eu(CH3COO)3, Gd(CH3COO)3, Tb(CH3COO)3, Dy(CH3COO)3, Ho(CH3COO)3, Er(CH3COO)3, Tm(CH3COO)3, Yb(CH3COO)3, Lu(CH3COO)3, Y(CH3COO)3, and Sc(CH3COO)3. Preferably, the organic solvent is selected from at least one of oleic acid, oleylamine, trioctylamine and octadecene.
7. The method according to claim 5 or 6, characterized in that: The molar ratio of B salt and Ln salt is (1-x):x. Preferably, the amount of hydrofluoride A used is 1 to 5 times the sum of the molar numbers of B salt and Ln salt.
8. The method according to any one of claims 5 to 7, characterized in that: The method further comprises: dispersing the rare earth doped ABF3 perovskite type nano luminescent material in a non-polar organic solvent to obtain a rare earth doped ABF3 perovskite type nano luminescent material solution.
9. The method according to claim 8, characterized in that The non-polar organic solvent is selected from at least one of n-hexane, cyclohexane, chloroform, dichloromethane or toluene.
10. Application of the material according to any one of claims 1 to 4 in the fields of fluorescence detection, biological imaging, super-resolution imaging, single-molecule tracing, optical anti-counterfeiting and coding.
Citation Information
Patent Citations
Rare earth-doped fluoride lanthanum potassium nano fluorescent marking material and preparation method thereof
CN102676172A
Method for preparing MF2 type water-soluble mesoporous light-emitting nanospheres in efficient and green mode
CN105713603A
Upconversion phosphor materials as well as preparation method and application thereof
CN107974251A
Nanometer photon avalanche fluorescence principle with nonlinear response cascade amplification effect and implementation method
CN113607705A
H < + > ion doped luminescence-enhanced rare earth inorganic nano luminescent material and preparation method and application thereof
CN116023944A
